Wordplay and World-Play: The Minima Visibilia in The Construction of Linguistic Sciences - Emad Abd Elkareem Alqadumi (JURNAL ARBITRER, 2019)
This paper aims to illustrate, by using a single sentence as the focus of the study, the inseparability of wordplay and worldplay. It intends to illustrate how playing with a sentence like "Wordplay was a game Shakespeare played competently" can help us understand the very complex and fascinating phenomena of language, endless play. At first glance, the sentence may appear to be giving a piece of information on the English Elizabethan dramatist. However, this same sentence can also be used to illustrate the countless possible interpretations of any discourse. In addition, the sentence can be used to illustrate how linguistic sciences such as phonetics, morphology, syntax, semantics, stylistics, psycholinguistics, sociolinguistics, comparative linguistics and discourse analysis separate some properties as representative of the entire science while suppressing all the others as insignificant in order to control the playfulness of language.